2011
DOI: 10.1177/0961203310397081
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal chronotropic reserve and heart rate recovery in patients with SLE: a case–control study

Abstract: Abnormal heart-rate (HR) response during or after a graded exercise test has been recognized as a strong and an independent predictor of all-cause mortality in healthy and diseased subjects. The purpose of the present study was to evaluate the HR response during exercise in women with systemic lupus erythematosus (SLE). In this case-control study, 22 women with SLE (age 29.5 ± 1.1 years) were compared with 20 gender-, BMI-, and age-matched healthy subjects (age 26.5 ± 1.4 years). A treadmill cardiorespiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
3
24
0
4
Order By: Relevance
“…In this sense, Prado et al [6] observed abnormal chronotropic response during cardiorespiratory exercise testing in SLE women. Moreover, prior evidence [21,25] has demonstrated lower oxygen pulse during cardiorespiratory exercise tests in SLE woman suggesting blunted inotropic response.…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 96%
See 4 more Smart Citations
“…In this sense, Prado et al [6] observed abnormal chronotropic response during cardiorespiratory exercise testing in SLE women. Moreover, prior evidence [21,25] has demonstrated lower oxygen pulse during cardiorespiratory exercise tests in SLE woman suggesting blunted inotropic response.…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 96%
“…A growing number of investigations have shown cardiorespiratory abnormalities during exercise in SLE patients [6,8,17,20]. In this sense, Prado et al [6] observed abnormal chronotropic response during cardiorespiratory exercise testing in SLE women.…”
Section: Aerobic Capacity In Sle Patientsmentioning
confidence: 98%
See 3 more Smart Citations